GREEN CONSUMPTION BEHAVIOR AND MEASURES TO PROMOTE GREEN CONSUMPTION BEHAVIOR OF THE STUDENTS AT PRINCE OF SONGKLA UNIVERSITY - Waijarean, Naprarath; Sa-u, Samsoo; Tansakul, Jirawat; Danteravanich, Somtip (Srinakharinwirot University Journal of Sciences and Technology, 2022)
This study was aimed (1) to examine the students’ perception and their green consumption behavior, (2) to investigate the factors influencing green consumption habits, (3) to evaluate the reduction value of carbon dioxide emissions from the student’s green consumption behavior and from the university’s policy, and (4) to propose the measures to increase the students’ awareness and behavior of the green consumption according to the university’s policy. The population included 243 students from all five campuses of Prince of Songkla University using stratified random sampling. The instruments employed in the study were a test, a perception test, a behavioral assessment test with the precision rate of 0.75, 0.76 and 0.84, the evaluation program on carbon footprint emission, and group discussion analysis. The findings revealed that the average level of the student’s green consumption perception was at 13.50. It was also found that 77% of the students perceived the green consumption knowledge from their lecturers by attending several campaigns such as Green University. The other channels of gaining knowledge were 68.30% from energy saving, 67.5% from the campaign banners, and 47.3% from the university website. In addition, the students' green consumption behavior was found at a high level which turning off the tap after use was ranked at the highest level ( = 4.49), followed by cleaning vegetables ( = 4.45) and unplugging equipment after use ( = 4.45), and overall, the behavior of talking, posting, sharing and participating in campaigning banners in various activities were revealed at the lowest average. The students' green consumption behavior was shown to be statistically significant (p = 0.01) and predictably (2.20%) related to their green consumption knowledge, making it a predictable factor with a statistical significance of. 0.05. In terms of carbon emission from the students’ green consumption behavior, it was found the average amount per person was at 4.18 tCO2e/year, which the highest average was at 1.97 tCO2e/year. As a result, it is recommended that the university should initially emphasize on educating students about green consumption, stimulating the selection of campaigning media which suitable for the student's lifestyle, and raising awareness on green consumption starting at the executive level. It is also suggested that the concrete measures and practical policies on green consumption be implemented at the operational level, the social media campaigns be increased, and the online communication channels be used to approach individuals in order to increase the awareness and to change the individual behavior in terms of dealing with the environmental changes more effectively.